Robust Cell Detection and Segmentation for Image Cytometry Reveal Th17 Cell Heterogeneity. Issue 4 (4th February 2019) - Tsujikawa, Takahiro; Thibault, Guillaume; Azimi, Vahid; Sivagnanam, Sam; Banik, Grace; Means, Casey; Kawashima, Rie; Clayburgh, Daniel R.; Gray, Joe W.; Coussens, Lisa M.; Chang, Young Hwan
Abstract: Image cytometry enables quantitative cell characterization with preserved tissue architecture; thus, it has been highlighted in the advancement of multiplex immunohistochemistry (IHC) and digital image analysis in the context of immune‐based biomarker monitoring associated with cancer immunotherapy. However, one of the challenges in the current image cytometry methodology is a technical limitation in the segmentation of nuclei and cellular components particularly in heterogeneously stained cancer tissue images. To improve the detection and specificity of single‐cell segmentation in hematoxylin‐stained images (which can be utilized for recently reported 12‐biomarker chromogenic sequential multiplex IHC), we adapted a segmentation algorithm previously developed for hematoxlin and eosin‐stained images, where morphological features are extracted based on Gabor‐filtering, followed by stacking of image pixels into n ‐dimensional feature space and unsupervised clustering of individual pixels. Our proposed method showed improved sensitivity and specificity in comparison with standard segmentation methods. Replacing previously proposed methods with our method in multiplex IHC/image cytometry analysis, we observed higher detection of cell lineages including relatively rare TH 17 cells, further enabling sub‐population analysis into TH 1‐like and TH 2‐like phenotypes based on T‐bet and GATA3 expression. Interestingly, predominance of TH 2‐like TH 17 cells was associated with human papilloma virus (HPV)‐negative status of oropharyngeal squamous cell carcinoma of head and neck, known as a poor‐prognostic subtype in comparison with HPV‐positive status. Furthermore, TH 2‐like TH 17 cells in HPV‐negative head and neck cancer tissues were spatiotemporally correlated with CD66b + granulocytes, presumably associated with an immunosuppressive microenvironment. Our cell segmentation method for multiplex IHC/image cytometry potentially contributes to in‐depth immune profiling and spatial association, leading to further tissue‐based biomarker exploration. © 2019 International Society for Advancement of Cytometry